ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI VARIABEL KESIAPAN UNTUK BERUBAH SEBAGAI VARIABEL INTERVENING DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 (Studi Pada Karyawan PT. PELNI Persero Jakarta ) - Faiz Saf’ani; Intan Ratnawati (Faculty of Economics and Business | Universitas Diponegoro, 2021)
The 4th development of Industrial Revolution gives effect in industrial sector including maritime industrial sector. In the existing of dynamical change, Organizational Culture needs special treatment to increase employee’s performance. Besides, in the process of change, the readiness for change existed in employee is also important thing that needs attention to gain changes (transformation) which is suitable with the organization’s purposes. This research aims to know and analyze the effect of organizational culture variable towards employee’s performance through their readiness for change as mediator in one of Indonesian State Owned-Enterprises (BUMN), PT. PELNI (Persero) Jakarta. Research sample are permanent employee in PT. PELNI (Persero) Jakarta and already joined the program of company culture internalization for the agent of changes. The analysis of data is done by validity test, reliability test, classic assumption test, Path analysis, T test, F test, coefficient of determination test, also sobel test to know the effect of mediation. The result of research shows that Organizational Culture gives positive and significant effects to employee’s performance and the readiness for change; The Readiness for change give positive and significant effects to employee’s performance. Besides, the variable of Readiness for Change is proved to be able to mediate the relationship between Organizational Culture and employee’s performance, although the indirect-effect is fewer than direct-effect, so that this research can be suggestion for future research to more explore the variable of readiness for change as independent variable in the context of Industrial Revolution 4.0.